Investment: Depth Classification Version of CC - Neelameghan, A. (Journal of Information and Knowledge, 1971)
A depth classification version of Colon Classification for compound subjects going with the Basic Subject "X65 Investment’" is given. The methodology of design is based on that for freely faceted classification. Economy in schedule building has been achieved by the use of different devices - such as, Subject Device wherever helpful, and also by using the schedules already available for the classification of compound subjects going with the Basic Subject "X62 Banking". An index to the schedule, and thirty examples classified according to the depth version, are given.